Peran Scaffolding pada Zone of Proximal Development (ZPD) Berdasarkan Teori Vygotsky di Kelas 2 SDN Sambikerep 1/479 Kota Surabaya - Furoivisha, Najwa Amalia; Hitta Alfi Muhimmah (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Learning in lower elementary school grades requires learning support tailored to the needs and developmental levels of students. One relevant approach to support this process is the application of scaffolding within the Zone of Proximal Development (ZPD) framework. This study aims to describe the forms and stages of scaffolding implementation, the role of teachers in optimizing students' ZPD, responses and development of student learning abilities, and the challenges and strategies teachers face in implementing scaffolding in second-grade classrooms at SDN Sambikerep 1/479. This study used a qualitative approach with a descriptive approach. The subjects included one second-grade teacher and second-grade students. Data collection was conducted through in-depth interviews, non-participatory observation, and documentation. Data were analyzed through coding, categorizing, and drawing conclusions based on the research focus. Data validity was strengthened through triangulation of sources and techniques. The results indicate that scaffolding implementation is not limited to academic activities but begins as teachers build relationships and become familiar with students' daily lives. Scaffolding is implemented in a gradual and flexible manner through non-academic mentoring, initial assistance, adjustments to task difficulty, and gradual withdrawal of support based on student development. Teachers act as facilitators in optimizing students' Zone of Proximal Development (ZPD) by recognizing individual abilities, providing contextual learning support, and managing the classroom to support the mentoring process. The implementation of scaffolding has a positive impact on student responses, demonstrated by increased self-confidence, learning independence, and positive social interactions. The main challenges in implementing scaffolding include differences in student abilities and limited learning time, which are addressed through adaptive and flexible learning strategies. This study concludes that the implementation of scaffolding that is sustainable and responsive to student needs can support the optimization of ZPD and the learning development of lower-grade students.